2001
DOI: 10.1002/1097-0142(20010601)91:11<1992::aid-cncr1224>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of pulmonary large cell neuroendocrine carcinoma and large cell carcinoma with neuroendocrine morphology

Abstract: BACKGROUND Large cell carcinoma has been classified as four potential types based on its neuroendocrine morphology and evidence of neuroendocrine differentiation discernible by immunohistochemistry or electron microscopy. However, the clinical relation among these four categories has not been clearly defined. In 1999, the World Health Organization (WHO) categorized large cell neuroendocrine carcinoma as a variant of large cell carcinoma. MATERIAL AND METHODS The authors analyzed 119 cases of large cell carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
112
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 171 publications
(124 citation statements)
references
References 18 publications
(19 reference statements)
9
112
1
2
Order By: Relevance
“…3 The LCNEC subgroup is a recently recognized pathologic entity 6,7 and accounts for < 5% of lung, digestive, or undetermined origin carcinomas. [8][9][10][11][12][13][14] LCNECs initially were characterized by an intermediate survival between well-differentiated NEC and SCC. 3 The question of whether LCNEC should be considered as part of the NET spectrum remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The LCNEC subgroup is a recently recognized pathologic entity 6,7 and accounts for < 5% of lung, digestive, or undetermined origin carcinomas. [8][9][10][11][12][13][14] LCNECs initially were characterized by an intermediate survival between well-differentiated NEC and SCC. 3 The question of whether LCNEC should be considered as part of the NET spectrum remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 We observed a 24% 5-year overall survival rate and a 31-month median survival in patients with poorly differentiated LCNEC patients, in line with previous studies that demonstrated a 5-year survival rate between 13% and 57%. 3,8,9,11,22,27,28 In the current study, a high mitotic count and a low number of neuroendocrine markers at immunohistochemistry emerged as prognostic factors for survival in patients with poorly differentiated LCNEC. For the first time, we have identified relevant prognostic impact for the mitotic count in poorly differentiated LCNEC: Patients with < 37 mitoses per 10 HPFs had tumors that were characterized by a less aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Large cell neuroendocrine carcinoma (LCNEC) is a rare subtype of neuroendocrine carcinoma that accounts for approximately 3% of lung cancers 1. The prognosis of patients with LCNEC is reported to be poor, with five‐year survival rates of 15–57% 2.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with LCNEC have an extremely poor prognosis since the biological behavior of LCNECs is similar to that of small cell lung carcinomas and LCNECs also have characteristics of high-grade neuroendocrine tumors (1)(2)(3)(4)(5)(6)(7)(8)(9). However, the treatment for patients with LCNEC has been based on non-small cell carcinomas.…”
Section: Introductionmentioning
confidence: 99%